Incidencia del sistema de información gerencial en la gerencia departamental: caso hospital ESSALUD - Huánuco. - Coronado Chang, Ernesto Chiu (2003)
Incidencia del sistema de información gerencial en la gerencia departamental: caso hospital ESSALUD - Huánuco.